2016
DOI: 10.1111/jce.12947
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcomes by Sex in Arrhythmogenic Right Ventricular Cardiomyopathy: Findings from the North American ARVC Registry

Abstract: Clinical Presentation and Outcomes Background Sex differences in clinical presentation and outcomes of hereditary arrhythmias are commonly reported. We aimed to compare clinical presentation and outcomes in men and women with arrhythmogenic right ventricular cardiomyopathy (ARVC) enrolled in the North American ARVC Registry. Methods A total of 125 ARVC probands (55 females, mean age 38 ± 12; 70 males, mean age 41 ± 15) diagnosed, as either “affected” or “borderline” were included. Baseline clinical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…Based on clinical experience and the current literature, particularly a recent published meta-analysis 13 and a prognostic model for predicting incident sustained VA in patients with ARVC, 2 8 potential predictors were preselected and recorded at the time of diagnosis. 2 , 11 15 These were sex, age at diagnosis, recent (<6 months) cardiac syncope, number of premature ventricular complexes (PVCs) on 24-hour Holter monitoring, prior sustained VA events, number of anterior and inferior leads with T-wave inversion (TWI), and left and right ventricular ejection fraction (RVEF). The definitions for these predictor variables are presented in Table II in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Based on clinical experience and the current literature, particularly a recent published meta-analysis 13 and a prognostic model for predicting incident sustained VA in patients with ARVC, 2 8 potential predictors were preselected and recorded at the time of diagnosis. 2 , 11 15 These were sex, age at diagnosis, recent (<6 months) cardiac syncope, number of premature ventricular complexes (PVCs) on 24-hour Holter monitoring, prior sustained VA events, number of anterior and inferior leads with T-wave inversion (TWI), and left and right ventricular ejection fraction (RVEF). The definitions for these predictor variables are presented in Table II in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Men with ARVC are at higher arrhythmia risk than women 14, 41, 5154 . While the specific pathophysiologic basis for this observation is unclear it has been suggested that this may be due to a more frequent and intense exercise in men.…”
Section: Selected Topics In Risk Stratification Of Arvc Patientsmentioning
confidence: 99%
“…13,20,23,24,[62][63][64][65][66] The prognostic value of programmed ventricular stimulation in asymptomatic patients with ARVC remains unclear, but invasive evaluation of myocardial scar and fragmented, delayed electrograms may provide incremental information regarding SCD risk. 63,64,67 ICD therapy reduces SCD in high-risk patients with ARVC, but ICD implantation carries risks of complication, particularly lead-related adverse events and inappropriate shocks in younger patients.…”
Section: Sudden Death Riskmentioning
confidence: 99%